2018
DOI: 10.1007/s10840-018-0417-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimally interrupted novel oral anticoagulant versus uninterrupted vitamin K antagonist during atrial fibrillation ablation

Abstract: Purpose The safety and efficacy of a minimally interrupted novel oral anticoagulant (NOAC) strategy at the time of atrial fibrillation (AF) ablation is uncertain. The purpose of this study was to compare rates of bleeding and thromboembolic events between minimally interrupted NOAC and uninterrupted vitamin K antagonist (VKA) in patients undergoing AF ablation. Methods This was a retrospective single-center cohort study of consecutive patients who underwent AF catheter ablation between January 2013 and April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Subsequently, the large randomised ABRIDGE‐J trial showed that there were fewer major bleeding events in the MI‐dabigatran group compared with UI‐VKA without an increase in thromboembolic events 36 . Moreover, recently, a Netherland study also showed MI‐NOAC therapy was associated with fewer clinically relevant non‐major bleeding events compared with UI‐VKA, without compromising thromboembolism‐related safety within 1 month of the AF ablation 37 . In all, the above‐mentioned studies report the outcomes of comparisons between NOACs with no (or minimal) interruption and UI‐VKA, and it is uncertain whether such results can be extrapolated to UI‐NOAC versus MI‐NOAC.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the large randomised ABRIDGE‐J trial showed that there were fewer major bleeding events in the MI‐dabigatran group compared with UI‐VKA without an increase in thromboembolic events 36 . Moreover, recently, a Netherland study also showed MI‐NOAC therapy was associated with fewer clinically relevant non‐major bleeding events compared with UI‐VKA, without compromising thromboembolism‐related safety within 1 month of the AF ablation 37 . In all, the above‐mentioned studies report the outcomes of comparisons between NOACs with no (or minimal) interruption and UI‐VKA, and it is uncertain whether such results can be extrapolated to UI‐NOAC versus MI‐NOAC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients using vitamin K antagonist (VKA) underwent the procedure using uninterrupted anticoagulation with a target international normalized ratio (INR) between 2.0 and 3.0. Patients using non-vitamin-K oral anticoagulants (NOAC) skipped their dose on the morning of the procedure as previously described [ 8 ]. To exclude LA thrombi, all patients underwent transesophageal echocardiogram within 24 h of the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous pieces of research have been conducted on the administration of oral anticoagulation during PVI. The feasibility, efficacy, and safety of DOACs in the context of PVI have been highlighted in particular by four RCTs with a comparable study design [ 72 , 73 , 74 , 75 , 76 ]. Randomised control trials [ 77 , 78 , 79 ], as well as the current European and American Guidelines [ 34 , 80 ], indicate that uninterrupted (or little interrupted) DOACs offer a reliable substitute for a continuous-VKA approach, with a low risk of thromboembolic events and haemorrhage.…”
Section: Pulmonary Vein Isolation (Pvi) Ablationmentioning
confidence: 99%